STUDENTS' AND LECTURERS' PERCEPTIONS ON TEACHING MATERIALS AND METHODS IN THE SUBJECT OF PRINCIPLES OF TRANSLATING - Intan Yudha Pertiwi, - (2005)
Since English has been used as an international language, many sources of information are now available in English all over the world. For the countries in which English is the second or even the first language, a lot of information are easily accessed and used. But for the countries in which English is the foreign language, English can be a language barrier to the abundant information. Therefore, the role oftranslators is very important, particularly in Indonesia. English Department of UPI is one department which teaches translation. Before really able to translate, the students should be able to understand the principles. The subject of Principles of Translating is given as the first subject in Translating-Interpreting subject series. Various materials and methods are used, which in turn affect students' comprehension to the content of the subject and their perception to it. Therefore, this study attempts to present a brief portrait of students and lecturers' perceptions on the teaching materials and methods, students' problems encountered in the subject, lecturers' problems in. preparing teaching materials and methods, and students' expectation to the subject. This study used descriptive method. The data were collected from 29 students of class A and B year 2003 (semester four) who have taken Principles of Translating by using open-ended and closed-ended questionnaire. Two lecturers who taught these two classes were interviewed. All problems of the study have been answered. The result of the study shows positive perception from both classes and the lecturer as well. Both lecturers do not find meaningful problems in preparing teaching materials and methods. However, students' problems lie in the difficult words of the textbook that in turn influence their comprehension. Students' expectations are the use of simpler English words, the additional practice of translating in the subject, and more interesting method.